Saved : a war reporter's mission to make it home - Hall, Benjamin (New York : Harper, an imprint of HarperCollinsPublishers, 2023)
When veteran war reporter Benjamin Hall woke up in Kyiv on the morning of March 14, 2022, he had no idea that, within hours, Russian bombs would nearly end his life. As a journalist for Fox News, Hall had worked in dangerous war zones like Syria and Afghanistan, but with three young daughters at home, life on the edge was supposed to be a thing of the past. Yet when Russia viciously attacked Ukraine in February 2022, Hall quickly volunteered to go. A few weeks later, while on assignment, Hall and his crew were blown up in a Russian strike. With Hall himself gravely injured and stuck in Kyiv, it was unclear if he would make it out alive.
Keywords: Hall, Benjamin; Hall, Benjamin -- Health; Television journalists -- Biography; War correspondents -- Biography; Ukraine -- History -- Russian Invasion, 2022- -- Personal narratives, American; Ukraine -- History -- Russian Invasion, 2022- -- Journalists; Biographies; Personal narratives